Evaluating metal constraints for photovoltaics: Perspectives from China's PV development. (15th January 2021) - Ren, Kaipeng; Tang, Xu; Höök, Mikael
Highlights: Substantial increase of metal demand in China's PV sector will happen up to 2050. The general scarcities of both base metal and byproduct metal have been found. Uncertainties lead to the furcation of metal requirement in China's PV sector. Two strategies to lessen metal supply risk have been put forward and discussed. The energy-metal nexus is essential for China's low-carbon energy transition. Abstract: Chinese PV industry can be expected to grow rapidly of until 2050, driven by ongoing decarbonization of the energy mix. Such large-scale deployments generate significant increases in metal demand that may induce resource dilemmas. In this study, dynamic material flow analysis is combined with scenario analysis to estimate future metal demand from Chinese PV industry and complemented by a supply risk assessment. It is found that the maximum annual copper and silver demand up to 2050 equals 79.6% and 58.5% of China's annual production in 2019. Similarly, the baseline scenario projects maximum annual demand of Tellurium and Indium corresponding to 598.1% and 161.8% of China's annual production in 2019. Cumulative base metal demand by 2050 for China's PV sector is 17.3–22.8 times that of in 2018, while cumulative silver demand increases by 4.5–6 times from 2018 to 2050. In the baseline scenario, cumulative byproduct metal demand by 2050 is 14–27.3 times larger than in 2018. High annual and cumulative supply pressures indicate not only the general scarcity of base, precious, and byproduct metals but also highlights the importance of building stable trade relationships for future PV developments in China. Two different measures are identified and assessed for reducing short- and long-term supply risks. Prolonging the lifetime from 25 to 30 years can achieve a cumulative metal conservation of 6.7–24.2%, while shorter lifetime will give rise to secondary supply if recycling technologies are implemented. A clean energy shift indicates that metal availability will become an important perspective for assessing energy security, implying that resource constraints should be considered in different planning levels for renewable energy developments. Strong interconnections between energy and metal supply chains indicate that coordination and holistic nexus views are required for achieving simultaneous sustainability in both systems.